SEO OPTIMIZATION IN WEB RESOURCES MONITORING SYSTEM - АСТІСТОВА, Т. І. (Technologies and Engineering, 2023)
Goal. To develop a system for monitoring WEB sites based on the research of methods and software tools that are used to raise the position of the site in search engines and increase the visitor rating with the help of SEO optimization. Methodology. The development of the system was based on theoretical and experimental research, which is used to analyze services and programs for promoting the site to the top positions of search engines, professional analysis of parameters, re-engagement of customers and monitoring of sites on the Internet. Results. As a result of the study of site monitoring systems, services and software AddWeb, Google Analytics, Web Position Gold were developed and analyzed. Based on the analysis, certain shortcomings were identified, which prevent a more accurate analysis of the resource. Taking this into account, a monitoring system called "WebMonit" was developed in the form of a website. This system uses a complex method of performance analysis and testing of site accessibility parameters on the Internet, and the developed software modules – scripts make it possible to output results for analysis and resolution of problem detection/ This system checks resource elements that are important for search engine optimization. They include, in particular, tags, selection of keywords for which the resource is planned to be promoted, usability, ranking, semantic core of the site, content, user-friendly interface. If these elements are optimized, it is possible to display the resource in the TOP in search engines and the Internet. Scientific novelty. The proposed original solution in the form of a monitoring system that provides the opportunity to display not only the statistics of the site’s working condition, but also to find problems and provide advice on their elimination to improve SEO optimization and expansion of functionality in the decisions made. Practical significance. There are many tools for promoting a site on the Internet, each of which is effective in a specific aspect. The work gives comparative characteristics of the use of tools for site promotion, identified advantages and disadvantages of existing systems and developed a monitoring system called "WebMonit" in the form of a website that will improve site monitoring, and developed software modules – scripts will improve site promotion.